Coated nickel titanium archwires and their uncoated counterparts: In-vitro contemporary comparison of unloading forces - Maio Pinzan-Vercelino, Celia Regina; Gurgel, Julio de Araujo [UNESP]; Bramante, Fausto Silva; Pessoa, Thalita Fonseca; Albertin, Silvia Americo; Nogueira Fialho, Melissa Proenca; Pinzan, Arnaldo (Elsevier B.V., 2020)
Objective > To compare the unloading forces between aesthetic nickel titanium (NiTi) wires coated with rhodium and epoxy resin, as well as their uncoated equivalents. Additionally, intragroup comparisons between the different deactivation forces were evaluated, and the inner alloy cores were determined. Material and methods > Forty-four 0.018 '' NiTi wire segments were equally divided into 4 groups: E- NiTi coated with epoxy resin, C- NiTi uncoated, R- heat-activated NiTi coated with rhodium, and T- heat-activated NiTi uncoated. The unloading values were recorded at 0.5, 1, 2, and 3 mm using a 3-point bending test, according to the method in ISO Standard 15.841. Cross-sectional scanning electron microscopy was used to assess the inner alloy core thickness of the wires. Results > The intergroup comparison was successively: at 0.5 mm: E (1.21) > C (0.60) = R (0.63) = T (0.58); at 1 mm: E (1.30) = C (1.23) > R (0.91) = T (0.80); at 2 mm: C (1.93) > E (1.36) = R (1.20) and R (1.20) = T (1.00) and E (1.36) > T (1.00); at 3 mm: C (2.44) > R (2.02) > E (1.62) = T (1.68). The intragroup comparisons showed for all groups that the forces were statistically higher at 3 mm than the other deactivations (p < 0.01). Group E presented a reduced inner alloy core (.0155). Conclusion > The unloading forces demonstrated variability between the wires tested and between the different deactivations. Therefore, depending on the type of movement required and the periodontal conditions, orthodontists should pay attention during archwire selection.
Keywords: Orthodontic wires; Physical properties; Aesthetics; Orthodontic appliances; Fixed; Mechanical phenomena